2017
DOI: 10.3747/co.24.3828
|View full text |Cite
|
Sign up to set email alerts
|

Coming of Age in Canada: A Study of Population-Based Genetic Testing for Breast and Ovarian Cancer

Abstract: The BRCA1 and BRCA2 genes are the two most commonly mutated in hereditary breast and ovarian cancer, and they are the canonical pair when it comes to cancer testing 1 . There are many other candidate genes, and large-panel testing is increasingly the norm even though not all practitioners are in agreement 2 that testing for 20 genes is better than testing for 2. Mutations are associated with lifetime risks of 80% for breast cancer and 15%-40% for cancer of the ovary or fallopian tube for BRCA2 and BRCA1 respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…In recent years, several groups have called for broader access to BRCA genetic testing among Ashkenazi Jews and among women in the general population, which could enable women and men with a BRCA variant to learn their status, take steps to reduce their cancer risk, and encourage cascade testing of close family members [5][6][7]10,11 . Among Ashkenazi Jews, where testing for the three founder variants can identify most BRCA carriers, population-wide screening is cost-effective or even cost-saving 14 ; in other ethnicities, more comprehensive genetic testing would be required to identify most individuals carrying a BRCA variant, but depending on the source of testing, this may also be cost-effective 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several groups have called for broader access to BRCA genetic testing among Ashkenazi Jews and among women in the general population, which could enable women and men with a BRCA variant to learn their status, take steps to reduce their cancer risk, and encourage cascade testing of close family members [5][6][7]10,11 . Among Ashkenazi Jews, where testing for the three founder variants can identify most BRCA carriers, population-wide screening is cost-effective or even cost-saving 14 ; in other ethnicities, more comprehensive genetic testing would be required to identify most individuals carrying a BRCA variant, but depending on the source of testing, this may also be cost-effective 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have demonstrated that the prevalence of germline PVs and gene-specific risk estimates could change, not only based on family history and type/molecular subtype of the tumors but also on the basis of race, ethnicity and different geographic location [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…These individuals would likely not qualify for clinical genetic testing unless they developed cancer themselves, representing a missed opportunity for cancer prevention. Because BRCA variants predispose to very high breast and ovarian cancer risks even among carriers without a family history [5,9], these findings have spurred calls for broader access to BRCA genetic testing, among Ashkenazi Jews and in the general population [5-7,10,11].…”
Section: Introductionmentioning
confidence: 99%